Bonding Performance of CFRP-Steel Interface after Continuous High Temperature - Tian-Bao Gao; Peng-Xiang Ma; Guo-Min Zhao; Zhu-Hui Zhang; Xiao-Yao Yao (Advances in Materials Science and Engineering)
The bonded shear performance of CFRP-reinforced steel structures following continuous high-temperature natural cooling was investigated experimentally, and 30 CFRP-steel specimens were subjected to single-shear tensile testing. In analyzing the shear stress-displacement relationship in each working condition, the equation for the coupling effect of the heating temperature and duration on the ultimate shear stress was proposed. The results show that the ultimate shear stress at the CFRP-steel interface tends to decrease with the increase of heating temperature, and the ultimate shear stress at the heating temperature of 300°C is 32.37% of that at 25°C. The high-temperature duration has an obvious influence on the bonding performance of the CFRP-steel interface, and the CFRP-steel specimens fail when the heating temperature is 300°C and lasts for 120 min.